2008
DOI: 10.1111/j.1365-2621.2007.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties related to particle size distribution and composition in dark chocolate

Abstract: Composition in dark chocolate was varied and the effects determined on microstructure, using light microscopy, and mechanical properties of molten and tempered chocolates, using a TA.HD Plus Texture Analyser. Compositional parameters were particle size distribution (PSD) (D90 of 18, 25, 35 and 50 μm), fat (25%, 30% and 35%) and lecithin (0.3% and 0.5%) contents. Micrographs revealed wide variations in sugar crystalline network structure and inter-particle interaction strengths related to PSD and fat level. Sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 22 publications
9
71
1
1
Order By: Relevance
“…Previous studies have also shown that SSA is inversely correlated with the different components of the PSD (Afoakwa et al 2009;Beckett 1999;Sokmen and Gunes 2006;Ziegler and Hogg 1999), as was observed in this study. As a result, it was concluded that a variation in PSD may occur depending on the CaCO 3 content of chocolate, and that it is possible to observe a variation in the rheological, sensory and textural properties of the product due to this PSD variation.…”
Section: Particle Size Distributionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies have also shown that SSA is inversely correlated with the different components of the PSD (Afoakwa et al 2009;Beckett 1999;Sokmen and Gunes 2006;Ziegler and Hogg 1999), as was observed in this study. As a result, it was concluded that a variation in PSD may occur depending on the CaCO 3 content of chocolate, and that it is possible to observe a variation in the rheological, sensory and textural properties of the product due to this PSD variation.…”
Section: Particle Size Distributionsupporting
confidence: 89%
“…Traditionally, continental European chocolate has been described as having a fineness of 15-22 μm particle diameter, while North American chocolate has a corresponding value of 20-30 μm (Afoakwa et al 2009). Typically, values around 20 μm are used for standards (Schumacher et al 2009).…”
Section: Particle Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the QDA, the chocolate samples from the PH16 cultivar were characterized by significantly (p<0.05) greater firmness than the other two samples. The texture is one of principal factors used to evaluate the quality of the products by the consumers, and two other important factors are the appearance and flavor (AFOAKWA et al, 2009).…”
Section: Sensory Profiles Of Chocolates Produced From Cocoa Cultivarsmentioning
confidence: 99%
“…These properties are studied using many different experimental methods. A penetration test using a thin probe is an empirical method of assessing the mechanical properties of chocolate or confectionery products (Liang and Hartel, 2004;Do et al, 2007;Afoakwa et al, 2008Afoakwa et al, , 2009). This method has been used to study the effect of composition, particle size distribution, fat crystallization behaviour and tempering on the mechanical properties in chocolate bars (Afoakwa et al, 2008(Afoakwa et al, , 2009.…”
mentioning
confidence: 99%